HADIAH PERAYAAN YANG TIDAK SYAR’I - Muhamad Arifin (Al-Majaalis : Jurnal Dirasat Islamiyah, 2020)
Abstract In a democratic country, people have the freedom to worship according to their respective religions. One of the direct consequences of that principle, the creation of a heterogeneous society, Muslims live side by side with followers of other religions. Thus, every religious adherent is protected by law to celebrate various religious holidays, so that in the midst of one community, there are alternately celebrated holidays. Usually at every holiday celebration, they try to enliven it, including by serving a variety of special dishes in accordance with the greatness of the holiday. Usually, in every holiday celebration, they try to enliven it, including by serving a variety of special dishes in accordance with the greatness of the holiday. To add to the lively celebration of the holidays, the adherents of a religion also share happiness with the surrounding community. Some send foods, gifts and congratulations. There are also those who hold a banquet by inviting the surrounding community, both held at places of worship or at their homes. Muslims often argue in response to gifts or banquets from other faiths, whether to accept and eat the food or reject it. This study aims to answer this polemic, in order to help the community behave appropriately according to the sharia provisions.